Development and Characterisation of Antibody-Based Optical Imaging Probes for Inflammatory Bowel Disease - Matthijs David Linssen; Wouter Tjerk Rudolph Hooghiemstra; Annelies Jorritsma-Smit; Derk Pieter Allersma; Gerard Dijkstra; Wouter Bastiaan Nagengast (MDPI AG, 2021)
Monoclonal antibodies are an important addition to the medicinal treatment paradigm for IBD patients. While effective, these agents show a high degree of primary and secondary non-response, and methods to predict response are highly desired. Information on drug distribution at the target level is often lacking. Fluorescent endoscopic imaging using labelled antibody drugs may provide insight regarding drug distribution, target engagement and drug response, but these assessments require stable and functional fluorescently-conjugated probes. Infliximab, vedolizumab, adalimumab and ustekinumab were conjugated to IRDye 800CW, IRDye 680LT and ZW800-1. The resulting 12 tracer candidates were analysed and characterised on SE-HPLC, SDS-PAGE, iso-electric focussing (IEF) and ELISA in order to evaluate their feasibility as candidate clinical tracers for cGMP development. Major differences in the conjugation results could be seen for each conjugated drug. For Infliximab, 2 conjugates (800CW and 680LT) showed formation of aggregates, while conjugates of all drugs with ZW800-1 showed reduced fluorescent brightness, reduced purification yield and formation of fragments. All 6 of these candidates were considered unfeasible. From the remaining 6, ustekinumab-680LT showed reduced binding to IL23, and was therefore considered unfeasible. Out of 12 potential tracer candidates, 5 were considered feasible for further development: vedolizumab-800CW, vedolizumab-680LT, adalimumab-800CW, adalimumab-680LT and ustekinumab-800CW. Infliximab-680LT and ustekinumab-680LT failed to meet the standards for this panel, but may be rendered feasible if tracer production methods were further optimized.